Developing of an Android – Based Application for Computer Based National Assesment (ANBK) Try Out - Sipahutar, Lahmudin; Handayani, Nursyah (International Journal of Computer and Information System (IJCIS), 2024)
Direct observations were made of the process of carrying out trial tests (try outs) as well as student assessments at Bina Satria Mulia Middle School. This application is designed to prepare students for the Computer-Based National Assessment (ANBK) at the junior high school level. However, in its implementation, there are still obstacles such as the processing process, distribution of questions and answer sheets, as well as correction and assessment which takes time due to the large number of trial test participants. In the application being built, a randomization method called Linear Congruent Method (LCM) will be applied. And the application of this method aims to randomize the order of the questions so that they are not always the same, so that students can practice and understand the contents of the questions. It is hoped that with this try out application for Course and Training Institutions, the try out process can be more efficient and improve its image. Course and Training Institute.